2006
DOI: 10.1130/g22282.1
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Archean basement beneath the Yangtze craton

Abstract: The age distribution of the crust is a fundamental parameter in modeling continental evolution and the rate of crustal accretion through Earth's history, but this is usually estimated from surface exposures. The exposed Yangtze craton in eastern China consists mainly of Proterozoic rocks with rare Archean outcrops. However, the U-Pb ages and Hf isotope systematics of xenocrystic zircons brought to the surface in lamproite diatremes from three Proterozoic outcrop areas of the craton suggest the widespread prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
192
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(217 citation statements)
references
References 16 publications
10
192
0
2
Order By: Relevance
“…The basement rocks of the southern Yangtze Block are of Proterozoic and Archean age (2100e1700 Ma and 2800e2300 Ma, respectively) (Metcalfe, 2006;Zheng et al, 2006). The block is characterized by Neoproterozoic magmatic activity (1000e700 Ma) (Chen and Jahn, 1998;, probably in response to the breakup of Rodinia Ling et al, 2003).…”
Section: Source Characteristics Of Surrounding Tectonic Unitsmentioning
confidence: 99%
“…The basement rocks of the southern Yangtze Block are of Proterozoic and Archean age (2100e1700 Ma and 2800e2300 Ma, respectively) (Metcalfe, 2006;Zheng et al, 2006). The block is characterized by Neoproterozoic magmatic activity (1000e700 Ma) (Chen and Jahn, 1998;, probably in response to the breakup of Rodinia Ling et al, 2003).…”
Section: Source Characteristics Of Surrounding Tectonic Unitsmentioning
confidence: 99%
“…The Yangtze Block is separated from the North China Craton by the Qinling-Dabie orogenic belt to the north and is bounded on the west and south by the Tibetan Plateau and Indochina Block, respectively. Archean and Proterozoic basement rocks have been recognized in southern Yangtze Block with zircon U-Pb ages at 2800e2300 Ma and 1700e2100 Ma (Qiu et al, 2000;Metcalfe, 2006;Zheng et al, 2006). Neoproterozoic magmatism (1000e700 Ma), including granites, volcanic rocks and ophiolites, occurred sporadically around the Yangtze Block (Li, 1999;Zhou et al, 2002Zhou et al, , 2006Xiao et al, 2007;Ye et al, 2007), which probably produced by the pre-breakup of Rodinia and subsequent migration of South China (Zhou et al, 2002;.…”
Section: Possible Sediment Sourcesmentioning
confidence: 99%
“…In addition, researchers have obtained ca. 2000 Ma zircon xenocryst ages (using LA-ICPMS, the majority of zircons have Th/U>1) in the lamproite around the Yangtze block [30]. Furthermore, 2091-2025 Ma old zircon ages were measured in Mesozoic zircons of the Tongling district, Anhui Province (SHRIMP method, Th/U is 0.15-0.46, with oscillatory zoning) [76].…”
Section: Tectonic Significance Of Paleoproterozoic Rapakivi Granites mentioning
confidence: 99%
“…Kongling Complex) are rare in the Yangtze block [25][26][27][28]. Even so, recent studies have shown that there are chronological records of 1.8-2.1Ga tectonothermal events in the Yangtze block [29][30][31][32][33][34][35][36][37][38]. Some of these studies indicates that these events may be related to the amalgamation and breakup of the Columbia supercontinent [34][35][36][37][38].…”
mentioning
confidence: 99%